Composición química de ensilaje de maíz forrajero (ZEzea mays) y cáscara de plátano verde (musa paradisiaca) en diferentes proporciones en una dieta base - Mera Macías, Nathaly Sullyn (2022)
The research was carried out at the "La María" campus of the Quevedo State Technical University (UTEQ), the objective of this research was to evaluate the chemical composition and aerobic stability of forage corn silage and green banana peel in different proportions in a base diet, a completely randomized design was applied, with four treatments and four repetitions, where the level of inclusion of the agro-industrial by-product of green plantain was evaluated, plus a control treatment of corn forage, with a fermentation time of 30 days. . The significance of the data obtained was evaluated through an analysis of variance. The study of the treatments allowed to know the chemical composition dry matter (DM), organic matter (MO), inorganic matter (MI), crude fiber (FC), crude protein (PC), fat (EE), fiber fractions: fiber neutral detergent fiber (NDF), acid detergent fiber (FDA) and raw energy (CE). The results obtained from MS, MO, MI, EE, FB indicate that there were no significant differences between treatments (p > 0.05); while the fiber fractions, NDF and FDA presented similar trends in the evaluated treatments (p > 0.05) and the EC their behavior did not show differences between treatments (p > 0.05). The increase in agro-industrial residue green banana peel in a base diet did not present significant differences, although its nutritional value improved, it´s recommended to use levels higher than those used in the present investigation.